Transcriptional profiling of human macrophages during infection with Bordetella pertussis - Petráčková, Denisa; Farman, Mariam R; Amman, Fabian; Linhartová, Irena; Dienstbier, Ana; Kumar, Dilip; Držmíšek, Jakub; Hofacker, Ivo; Rodriguez, Maria Eugenia; Večerek, Branislav (RNA biology, 2020)
Bordetella pertussis, a strictly human re-emerging pathogen and the causative agent of whooping cough, exploits a broad variety of virulence factors to establish efficient infection. Here, we used RNA sequencing to analyse the changes in gene expression profiles of human THP-1 macrophages resulting from B. pertussis infection. In parallel, we attempted to determine the changes in intracellular B. pertussis-specific transcriptomic profiles resulting from interaction with macrophages. Our analysis revealed that global gene expression profiles in THP-1 macrophages are extensively rewired 6 h post-infection. Among the highly expressed genes, we identified those encoding cytokines, chemokines, and transcription regulators involved in the induction of the M1 and M2 macrophage polarization programmes. Notably, several host genes involved in the control of apoptosis and inflammation which are known to be hijacked by intracellular bacterial pathogens were overexpressed upon infection. Furthermore, in silico analyses identified large temporal changes in expression of specific gene subsets involved in signalling and metabolic pathways. Despite limited numbers of the bacterial reads, we observed reduced expression of majority of virulence factors and upregulation of several transcriptional regulators during infection suggesting that intracellular B. pertussis cells switch from virulent to avirulent phase and actively adapt to intracellular environment, respectively.
Keywords: kultivované buňky; Cell Line; Reproducibility of Results; infection; Gene Expression Profiling; Real-Time Polymerase Chain Reaction; reprodukovatelnost výsledků; intracellular survival; výpočetní biologie; Gene Ontology; transkriptom; Gene Expression Regulation; macrophage; Whooping Cough; genové regulační sítě; Transcriptome; Gene Regulatory Networks; kvantitativní polymerázová řetězová reakce; Host-Pathogen Interactions; regulace genové exprese; Cells, Cultured; Bordetella pertussis; pertuse; Macrophages; Humans; interakce hostitele a patogenu; host-pathogen interaction; makrofágy; stanovení celkové genové exprese; buněčné linie; Computational Biology; genová ontologie; lidé